Learning Leadership of School Aministrators Affecting Learning Management Efficiency of Teachers in Schools under Nakhon Phanom Primary Educational Service Area Office 1 - Khammee, Mallika; Phengsawat , Waro; Pheasa, Akkaluck (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to study the learning leadership of school administrators affecting the efficiency of teachers’ learning management in schools under Nakhon Phanom Primary Educational Service Area Office 1. The sample consisted of 345 administrators and teachers in the academic year 2024, selected through multistage random sampling. The instruments were five-point rating scale questionnaires with reliability values ranging from 0.97 to 0.98. Statistical analyses included mean, standard deviation, Pearson correlation coefficient, and stepwise multiple regression analysis. The findings revealed that 1) Learning leadership of administrators was at a high level; 2) Teachers’ learning management efficiency was at a high level; 3) Learning leadership of administrators had a positive correlation with teachers’ learning management efficiency at the .01 significance level; 4) Predictors of learning management efficiency were self-directed learning, creativity, and team learning and 5) Development guidelines comprised three aspects, three objectives, nine key results, and 27 guidelines, evaluated as most appropriate and feasible.